The Influence of Liquidity Ratio and Cash Flows from Operation Ratio on the Return on Investment and Future Profit of Listed Companies in Property and Construction of Thailand - Worasinpan, Mintita; Saengkeaw, Porntiwa (Journal of Modern Learning Development, 2022)
The purposes of this study were to study 1) The influence of liquidity ratio and cash flows from operation ratio on the return on stock investment of listed companies in property and construction of Thailand. 2) The influence of liquidity ratio and cash flows from operation ratio on and future profit of listed companies in property and construction of Thailand. The 3-year data were from the year 2018 to 2020. The data comprised of 93 t listed companies in The Market for Alternative Investment all so had not random sampling, by using record form for collecting secondary information from annual financial statements from www.setsmart.com The statistics including the Pearson’s correlation, the descriptive statistics, and the relationships were computed using multiple regression. Dependent variable are on the return on stock investment and future profit are return on assets ratio. The following were the results 1) The influence of liquidity ratio and cash flows from operation ratio on the return on stock investment. Liquidity ratio are current ratio, quick ratio, receivable turnover, collection period, inventory turnover had not a significant effect to the return on stock investment. Cash flows from operation ratio are cashflow from operating activities per total liabilities, cashflow from operating activities per average total assets and cashflow from operating activities per net profit had not a significant effect to return on investment is the hypothesis 0.05 statistics significant level. 2) The influence of liquidity ratio and cash flows from operation ratio on the future profit. Liquidity ratio are current ratio, receivable turnover, collection period, inventory turnover had not a significant effect to the future profit but liquidity ratio are quick ratio had a significant effect to the future profit. Cash flows from operation ratio are cashflow from operating activities per total liabilities and cashflow from operating activities per net profit had not a significant effect to the future profit but cash flows from operation ratio are cashflow from operating activities per average total assets had a significant effect to the future profit is the hypothesis 0.05 statistics significant level.